Construction of Crystalline One‐Dimensional Infinite Argentophilic Silver Alkynyl Assemblies and their Luminescence Properties. Issue 47 (5th December 2018) - Yang, Yang; Zhang, Shan‐Shan; Zhao, Quan‐Qin; Wang, Xing‐Po; Tung, Chen‐Ho; Sun, Di
Abstract : Four crystalline one‐dimensional (1‐D) silver alkynyl assemblies, namely, [Ag11 ( t BuC≡C)7 (CH3 COO)4 ] n (1 ), [Ag21 ( t BuC≡C)11 (PhCOO)10 ] n (2 ), [Ag16 ( m ‐F‐PhC≡C)12 (CF3 COO)4 (CH3 CN)4 ] n (3 ) and [Cl@Ag14 (PhC≡C)10 (CF3 SO3 )3 ] n (4 ). have been obtained by reacting polymeric [AgC≡CR] n with silver salts under mild solvothermal conditions. Compound1 and3 are coordination polymer of irregular silver alkynyl clusters. Compound2 consists of well‐defined parallel Ag3 triangles columns. Compound4 is chains of chloride templated cage‐like silver clusters. Compound2 –4 show temperature‐sensitive luminescent behaviors. Amongst, compound2 and3 display dual‐emissive characteristic at low temperature. By correlating the structures and properties of four silver compounds, we found that the non‐emissive behavior of compound1 could be tentatively assigned to the absence of any aryl groups on the ligands. Abstract : Four crystalline one‐dimensional (1‐D) silver alkynyl assemblies with infinite argentophilic interactions have been present. Three of them show temperature‐sensitive emissions with two ones displaying dual‐emissive characteristic at low temperature. The non‐emissive one indicates the importance of the aryl groups for luminescence in emissive silver compound constructions.